The Authority of the Police in Detention Viewed from the Principle of Presumption of Innocence in the Indonesian Criminal Justice System - Mohammad Yusuf Effendy; Miftakhul Huda (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The authority of the police to conduct detention in Indonesia is strictly governed by positive law, particularly the Criminal Procedure Code (KUHAP) and the Law on the Indonesian National Police. Detention is a temporary deprivation of liberty against a suspect to ensure the integrity of legal proceedings, prevent flight, destruction of evidence, or recidivism. Police may detain individuals suspected of crimes punishable by at least five years’ imprisonment, but such authority requires judicial approval and must comply with the principles of legality, proportionality, and respect for human rights as outlined in relevant regulations. Detention procedures must align with the presumption of innocence, ensuring that suspects are not treated as guilty prior to a final court decision. KUHAP mandates strict time limits and judicial oversight, while suspects retain key rights including legal assistance, the right to be informed of the reasons for detention, and the right to challenge the legality of detention through pretrial motions. Abuse of detention authority can be curtailed through mechanisms such as detention suspension requests, pretrial reviews, internal police supervision, and external oversight institutions. These measures are crucial to maintaining accountability, preventing arbitrary detention, and upholding the fundamental rights of individuals within the criminal justice system.